Where Is love, Biscuit? : a pet & play book - Capucilli, Alyssa Satin, 1957- (HarperFestival, 2009)
"Where is love, Biscuit? Discover all the wonderful places where love can be found in this delightful touch-and-feel adventure!"--P. [4] of cover.